PERAN GURU PPKN DALAM MENINGKATKAN KEMAMPUAN KERJA SAMA PESERTA DIDIK DI SMP NEGERI 22 SEMARANG - Astuti, Desta Widya; Sutono, Agus; Ginting, Rosalina (FPIPSKR Universitas PGRI Semarang, 2026)
The research stems from the observed inadequacy of students' cooperative skills within the learning environment and the suboptimal role of Civic Education (PPKn) teachers in enhancing these competencies. This study aims to analyze the role of PPKn teachers in fostering students' cooperative skills at SMP Negeri 22 Semarang. Employing a descriptive qualitative research design, the findings reveal several key dimensions of the teachers' roles: 1) As Learning Facilitators, teachers engage students in collaborative projects and cultivate an interactive classroom climate; 2) As Discussion Directors, they provide encouragement, establish a non-threatening atmosphere, and mediate the exchange of perspectives; 3) As Autonomy Coaches, they underscore the significance of personal accountability through contextual learning approaches; 4) As Moderators, they demonstrate command of subject matter, effective classroom management, motivational techniques, and judicious time allocation; 5) As Learning Resource Developers, they create and utilize diverse instructional materials, including presentation modules (e.g., PPT); 6) As Evaluators and Monitors, they conduct systematic planning, encompassing the design of learning objectives and the implementation of assessment rubrics. In conclusion, the role of PPKn teachers at SMP Negeri 22 Semarang in augmenting students' cooperative skills is largely effective, entailing well-considered pedagogical planning and strategic implementation.